Coal-based solid waste material as well as preparation method and application thereof

By using specific components and dosages of coal-based solid waste materials, including silicate cement clinker, metakaolin, fly ash, calcium carbide slag modified gypsum and exciters, the problem of insufficient mechanical properties of coal-based solid waste materials in building rubber sand is solved, and efficient resource utilization and cement performance improvement is achieved.

CN119841561APending Publication Date: 2025-04-18CHINA BUILDING MATERIALS ACADEMY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510043382.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

In the prior art, the mechanical properties of coal-based solid waste materials used in building rubber sand are insufficient, making it difficult to effectively replace cement clinker.

Method used

The coal-based solid waste material including 60-80 parts by weight of silicate cement clinker, 0-30 parts by weight of metakaolin, 1-30 parts by weight of fly ash, 3-10 parts by weight of calcium carbide slag modified gypsum, and 5-10 parts by weight of the exciter were prepared by mixing, drying, calcining and grinding.

Benefits of technology

It significantly improves the flexural strength and compressive strength of coal-based solid waste materials, can effectively replace some cement clinker, reduce waste emissions, improve resource utilization, and improve cement performance and application effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005237607590000131
    Figure BDA0005237607590000131
Patent Text Reader

Abstract

The invention belongs to the technical field of building materials, and particularly relates to a coal-based solid waste material and a preparation method and application thereof. The coal-based solid waste material comprises 60-80 parts by weight of Portland cement clinker, 0-30 parts by weight of metakaolin, 1-30 parts by weight of fly ash, 3-10 parts by weight of carbide slag modified gypsum and 5-10 parts by weight of an exciting agent; the coal-based solid waste material with specific components and dosage has excellent breaking strength and compressive strength when being applied to the building mortar, the coal-based solid waste can be reutilized, waste discharge is reduced, and the resource utilization rate is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of building materials, and in particular relates to a coal-based solid waste material and a preparation method and application thereof. Background Art

[0002] A large amount of coal-based solid waste, such as coal gangue, fly ash, and coal gasification fine slag, is generated during the mining, processing, and utilization of coal. Although coal-based solid waste has certain potential utilization value, the overall utilization rate is still relatively low. Traditional treatment methods such as landfill and stockpiling not only fail to effectively utilize resources, but may also cause secondary pollution. For the purpose of environmental protection and resource conservation, the development of high-activity coal-based solid waste mixed material preparation technology and its conversion into high-value-added products can promote the research and development and application of coal-based solid waste, and provide strong support for the resource utilization of coal-based solid waste and the green development of the building materials industry.

[0003] Cement and concrete materials are important material foundations of modern society. There are problems such as high CO2 emissions and high energy consumption in the production process. Both the cement building materials industry and the solid waste output industry are in urgent need of finding a low-carbon, low-energy, green, sustainable and healthy development path. Using mixed materials to partially replace cement clinker is one of the most effective ways to achieve the above goals, but the mechanical properties of building materials made by replacing part of cement clinker with mixed materials still need to be improved. Summary of the invention

[0004] Therefore, the technical problem to be solved by the present invention is to overcome the defect of insufficient mechanical properties of coal-based solid waste materials applied to building mortar in the prior art, thereby providing a coal-based solid waste material and a preparation method and application thereof.

[0005] To this end, the present invention provides the following technical solutions:

[0006] The first aspect of the present invention protects a coal-based solid waste material, wherein the coal-based solid waste material includes 60-80 parts by weight of Portland cement clinker, 0-30 parts by weight of kaolin, 1-30 parts by weight of fly ash, 3-10 parts by weight of carbide slag modified gypsum, and 5-10 parts by weight of an activator.

[0007] In the present invention, the silicate cement clinker meets the requirements of GB / T 21372 "Silica cement clinker"; silicate cement clinker is a commercially available dry material, and typically, but not limitingly, the water content of silicate cement clinker is less than 1wt%.

[0008] In the present invention, the metakaolin is prepared by taking coal-based kaolin as raw material and calcining at 600-900° C. for 1-7 hours, and the water content of the coal-based kaolin is less than 1wt%.

[0009] In the present invention, the fly ash meets the requirements of GB / T 1596 "Fly ash used in cement and concrete", and the water content of commercially available products is less than 1wt%.

[0010] In the present invention, the activator is solid, the water content of which is mainly crystal water and chemically bound water, and the dosage is very low, so there is no need to control water.

[0011] According to the present invention, the preparation method of carbide slag modified gypsum comprises the following steps: mixing carbide slag with gypsum, drying, calcining, grinding and screening to obtain carbide slag modified gypsum.

[0012] According to the present invention, the mass ratio of the carbide slag to gypsum is 1:2-5.

[0013] In the present invention, the mixing is conventional mixing in the art, and it is sufficient to mix evenly. Typically, but not limited to, the mixing is carried out in a high-speed mixer at room temperature for 10-30 minutes.

[0014] In the present invention, the drying is conventional mixing in the art, and the drying temperature and time can be adjusted according to the selected instrument. Typically, but not limitedly, the drying is carried out in a hot air dryer at a drying temperature of 100-150° C. After drying, the water content of the obtained product is less than 2wt%.

[0015] According to the present invention, the calcination temperature is 700-1000° C., and the calcination time is 0.5-2 h; alternatively, the calcination temperature is 800-950° C., and the calcination time is 1-1.5 h.

[0016] In the present invention, the grinding and screening are conventional operations in the art, grinding includes ball milling and vibration milling; screening includes vibration screen and air flow screen.

[0017] According to the present invention, the average particle size of the carbide slag modified gypsum is 10-40 μm.

[0018] In the present invention, the gypsum contains crystal water in addition to physically adsorbed water and free water (the total water content of the two parts is estimated to be about 10%). However, the amount of gypsum used is relatively small, and the amount of water introduced into the system is also very small, so no special control is required.

[0019] According to the present invention, the coal-based solid waste material includes 65-70 parts by weight of Portland cement clinker, 0-15 parts by weight of kaolin, 10-25 parts by weight of fly ash, 5-8 parts by weight of carbide slag modified gypsum, and 6-8 parts by weight of an activator.

[0020] In the present invention, the high-alkaline soil is a conventional high-alkaline soil in the art. Typically, but not limitingly, the high-alkaline soil comes from coal-based solid waste materials, which is coal-bearing kaolin.

[0021] According to the present invention, the fly ash includes at least one of PC fly ash and CFB fly ash.

[0022] According to the present invention, the compressive strength activity index of the PC fly ash is 50-95%, and can be optionally 80-90%.

[0023] According to the present invention, the compressive strength activity index of the CFB fly ash is 50-75%, and can be optionally 60-70%.

[0024] In the present invention, PC fly ash is "powder coal furnace fly ash", which is industrial solid waste discharged during the combustion process of coal-fired power plant boilers and has high activity; while CFB fly ash is "circulating fluidized bed fly ash", which is fly ash discharged from circulating fluidized bed boilers and has rough particles, loose and porous surface, and relatively high activity.

[0025] In the present invention, the compressive strength activity index material is the data obtained after a stable age, generally the data after 28 days (including 28 days).

[0026] According to the present invention, when the fly ash includes PC fly ash and CFB fly ash, the mass ratio of the PC fly ash to the CFB fly ash is 1-3:1; optionally 1-2:1.

[0027] According to the present invention, the gypsum includes desulfurized gypsum and / or phosphogypsum; desulfurized gypsum may be selected.

[0028] According to the present invention, the activator includes a calcium-containing activator and / or a sodium-containing activator; optionally, the activator includes at least one of calcium formate, calcium lignin sulfonate, calcium chloride, sodium sulfate, sodium carbonate, sodium hydroxide, and sodium silicate.

[0029] According to the present invention, the water content of the coal-based solid waste material is less than 3wt%.

[0030] According to the present invention, the average particle size of the coal-based solid waste material is 20-80 μm.

[0031] The second aspect of the present invention protects a method for preparing a coal-based solid waste material, wherein the components in the aforementioned coal-based solid waste material are mixed, dried, and ground to obtain the coal-based solid waste material.

[0032] In the present invention, the mixing method is a conventional mixing method in the art, and typically, but not limitingly, the mixing method is homogenization.

[0033] A third aspect of the present invention protects a construction mortar, wherein the construction mortar comprises the aforementioned coal-based solid waste material or the coal-based solid waste material prepared by the aforementioned preparation method.

[0034] The technical solution of the present invention has the following advantages:

[0035] 1. The present invention provides a coal-based solid waste material, wherein the coal-based solid waste material includes 60-80 parts by weight of silicate cement clinker, 0-30 parts by weight of metakaolin, 1-30 parts by weight of fly ash, 3-10 parts by weight of carbide slag modified gypsum, and 5-10 parts by weight of an activator; in the present invention, the coal-based solid waste can be reused, waste discharge can be reduced, and resource utilization can be improved, and the coal-based solid waste material with specific components and dosage has excellent flexural strength and compressive strength when applied to building mortar. The carbide slag modified gypsum, the specific component of which includes calcium hydroxide, can significantly improve the alkalinity of gypsum, help promote the hydration reaction of gypsum, and generate hydration products such as hydrated calcium silicate (CSH gel) and hydrated calcium aluminate. These hydration products are the main source of strength of cementitious materials, can fill pores, improve density and strength, and thus further improve the performance and application effect of cement.

[0036] 2. The synergistic effect of metakaolin, PC fly ash and CFB fly ash in the present invention can further promote the hydration reaction of coal-based solid waste materials, thereby further improving the performance of the materials.

[0037] 3. In the present invention, the inventor unexpectedly found that when PC fly ash and CFB fly ash are used together, they have a better effect. The inventor speculates that there are mainly three reasons. The first is the synergy in physical properties. PC fly ash has many spherical particles and a smooth surface, which has a good lubricating effect, can reduce the water demand of building mortar and improve fluidity; CFB fly ash has irregular particles and may contain more pores and microcracks. These structural characteristics make it have stronger adsorption capacity and higher specific surface area. In building mortar, the particles of PC fly ash and CFB fly ash can fill each other to form a more compact stacking structure. This helps to reduce porosity and improve the density and strength of the material. At the same time, the adsorption capacity of CFB fly ash can absorb more moisture and admixtures, thereby improving the working performance and durability of building mortar. The second is the complementarity of chemical components. When PC fly ash and CFB fly ash are used together, their chemical components can complement each other to form a more comprehensive active substance system. This helps to improve the overall performance of building mortar, such as improving strength, durability and impermeability. The third is that when PC fly ash and CFB fly ash are actually used, the reaction mechanism promotes each other. In the preparation process of building mortar, the active substances in PC fly ash and CFB fly ash can react with the hydration products in cement clinker to form new hydration products. These hydration products can block pores and improve the density and strength of the material. At the same time, the desulfurization products and incompletely reacted desulfurizers in CFB fly ash may also participate in the hydration reaction, further improving the performance of the material. PC fly ash and CFB fly ash have certain complementarity and synergy in terms of chemical composition, physical properties and reaction mechanism. This makes it possible to produce better effects when the two are used together, such as improving the strength, durability and impermeability of concrete or cement-based materials.

[0038] 4. The specific dosage of PC fly ash and CFB fly ash in the present invention can further achieve the complementarity of chemical components and the synergistic effect of physical properties, while promoting the hydration reaction, increasing the density and strength of the material and further improving the performance of the material. DETAILED DESCRIPTION

[0039] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0040] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0041] In order to facilitate comparison between data, the compositions of specific raw materials used in the examples of the present invention and the comparative examples are the same.

[0042] Based on the mass of PC fly ash, PC fly ash includes SiO2: 48.5%, Al2O3: 27.0%, Fe2O3: 8.0%, CaO: 3.5%, MgO: 1.2%, K2O: 1.0%, Na2O: 0.4%, SO3: 0.2%, water content is 2%, and loss on ignition is 8.2%;

[0043] Based on the mass of CFB fly ash, CFB fly ash includes SiO2: 46.5%, Al2O3: 25.0%, Fe2O3: 10.0%, CaO: 3.5%, MgO: 2.2%, K2O: 1.0%, Na2O: 0.4%, SO3: 0.2%, water content is 2%, and loss on ignition: 9.2%;

[0044] In terms of territorial quality, kaolin includes SiO2: 46.0%, Al2O3: 39.5%, Fe2O3: 0.5%, TiO2: 0.1%, CaO: 0.3%, MgO: 0.2%, K2O: 0.2%, Na2O: 0.1%, water content is 2%, loss on ignition: 13.5%;

[0045] Desulfurized gypsum: CaSO4·2H2O accounts for 98.0%; water content is 2.0%;

[0046] The corresponding weight parts in the examples and comparative examples are 1 g.

[0047] Example 1

[0048] This embodiment provides a coal-based solid waste material, and the specific preparation method includes the following steps:

[0049] The preparation method of carbide slag modified gypsum comprises the following steps: mixing carbide slag and gypsum in a mass ratio of 1:4 in a high-speed mixer at room temperature for 20 minutes; placing the mixed product in an oven for drying at a drying temperature of 100° C., wherein the water content of the product obtained after drying is 1wt%; calcining the product obtained after drying at a calcination temperature of 850° C. for 1.5 hours; ball milling and vibration screening of the calcined product to obtain carbide slag modified gypsum with an average particle size of 20 μm;

[0050] The coal-based solid waste material comprises 70 parts by weight of silicate cement, 15 parts by weight of metakaolin, 5 parts by weight of PC fly ash (with a compressive strength activity index of 80% at 28 days), 5 parts by weight of CFB fly ash (with a compressive strength activity index of 70% at 28 days), 5 parts by weight of carbide slag modified gypsum, 0.5 parts by weight of calcium formate, and 6 parts by weight of sodium hydroxide; all the components are homogenized, dried, and ground to obtain the coal-based solid waste material;

[0051] The water content of the coal-based solid waste material is 2wt%; and the average particle size of the coal-based solid waste material is 80μm.

[0052] Example 2

[0053] This embodiment provides a coal-based solid waste material, and the specific preparation method includes the following steps:

[0054] Carry out the steps of preparing carbide slag modified gypsum in Example 1;

[0055] The coal-based solid waste material comprises 70 parts by weight of silicate cement, 5 parts by weight of metakaolin, 10 parts by weight of PC fly ash (with a compressive strength activity index of 80% at 28 days), 10 parts by weight of CFB fly ash (with a compressive strength activity index of 70% at 28 days), 5 parts by weight of carbide slag modified gypsum, 0.5 parts by weight of calcium formate, and 6 parts by weight of sodium hydroxide; all the components are homogenized, dried, and ground to obtain the coal-based solid waste material;

[0056] The water content of the coal-based solid waste material is 2wt%; and the average particle size of the coal-based solid waste material is 80μm.

[0057] Example 3

[0058] This embodiment provides a coal-based solid waste material, and the specific preparation method includes the following steps:

[0059] The method of Example 1 is different in that the preparation method of carbide slag modified gypsum includes the following steps: at room temperature, carbide slag and gypsum are mixed in a high-speed mixer at a mass ratio of 1:2 for 10 minutes; the mixed product is placed in a hot air dryer for drying at a drying temperature of 140°C, and the water content of the product obtained after drying is 1.2wt%; the product obtained after drying is calcined at a calcination temperature of 700°C for 2 hours; the calcined product is ball-milled and vibrated to obtain carbide slag modified gypsum with an average particle size of 35μm.

[0060] Example 4

[0061] This embodiment provides a coal-based solid waste material, and the specific preparation method includes the following steps:

[0062] Carry out the steps of preparing carbide slag modified gypsum in Example 1;

[0063] The coal-based solid waste material comprises 70 parts by weight of silicate cement, 12.5 parts by weight of metakaolin, 12.5 parts by weight of PC fly ash (with a compressive strength activity index of 80% at 28 days), 5 parts by weight of carbide slag modified gypsum, 0.5 parts by weight of calcium formate, and 6 parts by weight of sodium hydroxide; all the components are homogenized, dried, and ground to obtain the coal-based solid waste material;

[0064] The water content of the coal-based solid waste material is 2wt%; and the average particle size of the coal-based solid waste material is 80μm.

[0065] Example 5

[0066] This embodiment provides a coal-based solid waste material, and the specific preparation method includes the following steps:

[0067] Carry out the steps of preparing carbide slag modified gypsum in Example 1;

[0068] The coal-based solid waste material includes 70 parts by weight of silicate cement, 12.5 parts by weight of metakaolin, 12.5 parts by weight of CFB fly ash (with a compressive strength activity index of 70% at 28 days), 5 parts by weight of carbide slag modified gypsum, 0.5 parts by weight of calcium formate, and 6 parts by weight of sodium hydroxide; all the components are homogenized, dried, and ground to obtain the coal-based solid waste material;

[0069] The water content of the coal-based solid waste material is 2wt%; and the average particle size of the coal-based solid waste material is 80μm.

[0070] Example 6

[0071] This embodiment provides a coal-based solid waste material, and the specific preparation method includes the following steps:

[0072] Carry out the steps of preparing carbide slag modified gypsum in Example 1;

[0073] The coal-based solid waste material includes 70 parts by weight of silicate cement, 12.5 parts by weight of PC fly ash (with a compressive strength activity index of 80% at 28 days), 12.5 parts by weight of CFB fly ash (with a compressive strength activity index of 70% at 28 days), 5 parts by weight of carbide slag modified gypsum, 0.5 parts by weight of calcium formate, and 6 parts by weight of sodium hydroxide; all the components are homogenized, dried, and ground to obtain the coal-based solid waste material;

[0074] The water content of the coal-based solid waste material is 2wt%; and the average particle size of the coal-based solid waste material is 80μm.

[0075] Example 7

[0076] This embodiment provides a coal-based solid waste material, and the specific preparation method includes the following steps:

[0077] In the manner of Example 1, the difference is that the coal-based solid waste material includes 80 parts by weight of silicate cement, 12 parts by weight of metakaolin, 8 parts by weight of PC fly ash (with a compressive strength activity index of 80% at 28 days), 10 parts by weight of CFB fly ash (with a compressive strength activity index of 70% at 28 days), 8 parts by weight of carbide slag modified gypsum, 1 part by weight of calcium formate, and 8 parts by weight of sodium hydroxide;

[0078] The water content of the coal-based solid waste material is 2wt%; and the average particle size of the coal-based solid waste material is 80μm.

[0079] Example 8

[0080] This embodiment provides a coal-based solid waste material, and the specific preparation method includes the following steps:

[0081] In the manner of Example 1, the difference is that the coal-based solid waste material includes 60 parts by weight of silicate cement, 3 parts by weight of metakaolin, 5 parts by weight of PC fly ash (with a compressive strength activity index of 80% at 28 days), 5 parts by weight of CFB fly ash (with a compressive strength activity index of 70% at 28 days), 3 parts by weight of carbide slag modified gypsum, and 6.5 parts by weight of sodium hydroxide;

[0082] The water content of the coal-based solid waste material is 2wt%; and the average particle size of the coal-based solid waste material is 50μm.

[0083] Example 9

[0084] This embodiment provides a coal-based solid waste material, and the specific preparation method includes the following steps:

[0085] The method of Example 1 is followed, except that “5 parts by weight of PC fly ash (compressive strength activity index at 28 days is 80%), 5 parts by weight of CFB fly ash (compressive strength activity index at 28 days is 70%)” is changed to “5 parts by weight of PC fly ash (compressive strength activity index at 28 days is 70%), 5 parts by weight of CFB fly ash (compressive strength activity index at 28 days is 50%)”.

[0086] Example 10

[0087] This embodiment provides a coal-based solid waste material, and the specific preparation method includes the following steps:

[0088] The method of Example 1 is the same, except that "5 parts by weight of PC fly ash, 5 parts by weight of CFB fly ash" is changed to "6 parts by weight of PC fly ash, 4 parts by weight of CFB fly ash".

[0089] Embodiment 11

[0090] This embodiment provides a coal-based solid waste material, and the specific preparation method includes the following steps:

[0091] The method of Example 1 is followed, except that “15 parts by weight of kaolin, 5 parts by weight of PC fly ash (the compressive strength activity index at 28 days is 80%), and 5 parts by weight of CFB fly ash (the compressive strength activity index at 28 days is 70%)” is changed to “25 parts by weight of PC fly ash (the compressive strength activity index at 28 days is 80%)”.

[0092] Example 12

[0093] This embodiment provides a coal-based solid waste material, and the specific preparation method includes the following steps:

[0094] The method of Example 1 is followed, except that “15 parts by weight of kaolin, 5 parts by weight of PC fly ash (compressive strength activity index at 28 days is 80%), 5 parts by weight of CFB fly ash (compressive strength activity index at 28 days is 70%)” is changed to “25 parts by weight of CFB fly ash (compressive strength activity index at 28 days is 80%)”.

[0095] Comparative Example 1

[0096] This comparative example provides a coal-based solid waste material, and the specific preparation method includes the following steps:

[0097] The method of Example 1 is followed, except that "15 parts by weight of kaolin, 5 parts by weight of PC fly ash (the compressive strength activity index at 28 days is 80%), and 5 parts by weight of CFB fly ash (the compressive strength activity index at 28 days is 70%)" is changed to "25 parts by weight of kaolin".

[0098] Comparative Example 2

[0099] This comparative example provides a coal-based solid waste material, and the specific preparation method includes the following steps:

[0100] The coal-based solid waste material includes 50 parts by weight of silicate cement, 35 parts by weight of kaolin, 3 parts by weight of PC fly ash (with a compressive strength activity index of 80% at 28 days), 3 parts by weight of CFB fly ash (with a compressive strength activity index of 70% at 28 days), 1 part by weight of carbide slag modified gypsum, 0.3 parts by weight of calcium formate, and 2 parts by weight of sodium hydroxide; all the components are homogenized, dried, and ground to obtain the coal-based solid waste material.

[0101] The water content of the coal-based solid waste material is 2wt%; and the average particle size of the coal-based solid waste material is 20μm.

[0102] Comparative Example 3

[0103] This comparative example provides a coal-based solid waste material, and the specific preparation method includes the following steps:

[0104] The coal-based solid waste material comprises 95 parts by weight of silicate cement, 5 parts by weight of metakaolin, 5 parts by weight of PC fly ash (with a compressive strength activity index of 80% at 28 days), 5 parts by weight of CFB fly ash (with a compressive strength activity index of 70% at 28 days), 15 parts by weight of carbide slag modified gypsum, 5 parts by weight of calcium formate, and 15 parts by weight of sodium hydroxide; all the components are homogenized, dried, and ground to obtain the coal-based solid waste material;

[0105] The water content of the coal-based solid waste material is 2wt%; and the average particle size of the coal-based solid waste material is 80μm.

[0106] Comparative Example 4

[0107] This comparative example provides a coal-based solid waste material, and the specific preparation method includes the following steps:

[0108] The method of Example 7 is followed, except that "5 parts by weight of carbide slag modified gypsum" is changed to "5 parts by weight of desulfurized gypsum".

[0109] Test Case

[0110] The silicon-aluminum materials prepared in the embodiment and the comparative example were mixed and molded according to the provisions of GB / T17671 1999 "Test Method for Strength of Cement Mortar (ISO Method)", wherein the test specimens were prepared by mass, one part of silicon-aluminum material and three parts of Chinese ISO standard sand, with a water-cement ratio of 0.5, and prepared into prism specimens with a size of 40mm×40mm×160mm in width×height×length, and cured in water: the mortar specimens were demolded after being cured in a curing box at 20±2°C and relative humidity ≥90% for 1 day, and the demolded specimens were placed in water at 20±1°C for curing for 3 days and 28 days, and then the flexural strength and compressive strength were tested;

[0111] The specific test results are shown in Table 1.

[0112] Table 1

[0113]

[0114] Comparison of Example 1 with Comparative Examples 2 and 3 shows that the coal-based solid waste materials with specific components and dosages in the present invention have excellent flexural strength and compressive strength when applied to building mortar.

[0115] Comparing Example 1 with Examples 4-6, it can be seen that there is a synergistic effect among metakaolin, PC fly ash and CFB fly ash, which can further improve the performance of the material.

[0116] Comparing Example 1 with Examples 11 and 12, it can be seen that when PC fly ash and CFB fly ash are used together, they have a better effect.

[0117] By comparing Example 7 with Comparative Example 4, it can be seen that the specific components in carbide slag include calcium hydroxide, which can significantly increase the alkalinity of gypsum, help promote the hydration reaction of gypsum, and generate hydration products such as calcium silicate hydrate (CSH gel) and calcium aluminate hydrate; further improving the performance and application effect of cement.

[0118] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.

Claims

1. A coal-based solid waste material, characterized in that: The coal-based solid waste material comprises 60-80 parts by weight of silicate cement clinker, 0-30 parts by weight of metakaolin, 1-30 parts by weight of fly ash, 3-10 parts by weight of carbide slag modified gypsum, and 5-10 parts by weight of an activator.

2. The coal-based solid waste material according to claim 1, characterized in that: The preparation method of the carbide slag modified gypsum comprises the following steps: mixing carbide slag with gypsum, drying, calcining, grinding and screening to obtain the carbide slag modified gypsum.

3. The coal-based solid waste material according to claim 2, characterized in that: The mass ratio of carbide slag to gypsum is 1:2-5; and / or, after the drying, the water content of the obtained product is less than 2 wt%; And / or, the calcination temperature is 700-1000°C, and the calcination time is 0.5-2h; optionally, the calcination temperature is 800-950°C, and the calcination time is 1-1.5h; And / or, the average particle size of the carbide slag modified gypsum is 10-40 μm.

4. The coal-based solid waste material according to any one of claims 1 to 3, characterized in that: The coal-based solid waste material comprises 65-70 parts by weight of silicate cement clinker, 0-15 parts by weight of metakaolin, 10-25 parts by weight of fly ash, 5-8 parts by weight of carbide slag modified gypsum, and 6-8 parts by weight of an activator.

5. The coal-based solid waste material according to any one of claims 1 to 4, characterized in that: The fly ash includes at least one of PC fly ash and CFB fly ash; Optionally, the compressive strength activity index of the PC fly ash is 50-95%, optionally 80-90%; Optionally, the compressive strength activity index of the CFB fly ash is 50-75%, optionally 60-70%; Optionally, when the fly ash includes PC fly ash and CFB fly ash, the mass ratio of the PC fly ash to the CFB fly ash is 1-3:1; The ratio can be selected as 1-2:

1.

6. The coal-based solid waste material according to claim 2, characterized in that: The gypsum includes desulfurized gypsum and / or phosphogypsum; desulfurized gypsum can be selected.

7. The coal-based solid waste material according to any one of claims 1 to 6, characterized in that: The activator includes a calcium-containing activator and / or a sodium-containing activator; optionally, the activator includes at least one of calcium formate, calcium lignin sulfonate, calcium chloride, sodium sulfate, sodium carbonate, sodium hydroxide, and sodium silicate.

8. The coal-based solid waste material according to any one of claims 1 to 6, characterized in that: The water content of the coal-based solid waste material is less than 3wt%; And / or, the average particle size of the coal-based solid waste material is 20-80 μm.

9. A method for preparing coal-based solid waste materials, characterized in that: The components of the coal-based solid waste material according to any one of claims 1 to 7 are mixed, dried and ground to obtain the coal-based solid waste material.

10. A building mortar, characterized in that: The building mortar comprises the coal-based solid waste material described in any one of claims 1 to 8 or the coal-based solid waste material prepared by the preparation method described in claim 9.

Citation Information

Patent Citations

  • Complex Portland cement and preparation method and application thereof

    CN108455885A

  • Multi-scale solid waste modified phosphorus building gypsum composite cementing material

    CN114133201A

  • Coal-based solid waste geopolymer as well as preparation method and application thereof

    CN116282998A

  • Coal-based solid waste composite cementing material and preparation method thereof

    CN117567100A